Contribution of Janus-Kinase/Signal Transduction Activator of Transcription Pathway in the Pathogenesis of Vasculitis: A Possible Treatment Target in the Upcoming Future - Bursi, Roberto; Cafaro, Giacomo; Perricone, Carlo; Riccucci, Ilenia; Calvacchi, Santina; Gerli, Roberto; Bartoloni, Elena (Frontiers in Pharmacology, 2021)
Janus-kinase (JAK) and signal transduction activator of transcription (STAT) signal transduction pathway is involved in a wide range of physiological and pathological processes, including in the pathogenesis of several autoimmune diseases. Data supporting the role of JAK/STAT in the development of vasculitis are limited and mostly focused on large vessel vasculitis and Behçet’s disease. In this review, we provide a thorough picture of currently available evidence on the topic, gathered from in vitro experiments, animal models and human real-life data, analyzing the rationale for the use of JAK inhibitors for the management of vasculitis. Overall, despite a very strong biological and pathogenic basis, data are too few to recommend this therapeutic approach, beyond very severe and refractory forms of vasculitis. However, for the same reasons, a strong scientific effort in this direction is indeed worthwhile.